Determination of chloride threshold for corrosion of reinforcing steel bars in simulated pore solution using potentiodynamic techniques - Borgonia, Eden Marie B. (2009)
Pitting occurs in steel bars exposed to alkaline solution with sufficient chlorides. The corrosion susceptibility of steel bars in three different surface conditions, namely, as received, pre-rusted and polished was investigated by means of a potentiodynamic polarization technique. This method employed 0.9M NaOH and saturated Ca(OH)2 solutions simulating the pore liquid of alkaline concrete. Varying amount of NaCl was added to the simulated pore solution test the chloride threshold before pitting occurs. The nature and morphology of the corrosion pits were studied using scanning electron microscope (SEM) images. The susceptibility of the different surfaces, based on the anodic polarization curve was validated by the pitting observed under the SEM. The chloride threshold values for each of the surfaces was similar to published literature , with the as-received condition showing the highest chloride threshold. Higher alkalinity increased the chloride limit before passivity breakdown. Stirring of pore solution increased the passivation current, thereby increasing corrosion rate. The corrosion was more apparent in samples immersed in higher chloride containing environment. Corrosion pits initiate more readily in the smooth 600 grit condition, because of the absence of mill scale, but once corrosion was initiated, pre-rusted surfaces have a higher tendency to form well defined large pits.